1999
DOI: 10.1111/1469-8986.3640430
|View full text |Cite
|
Sign up to set email alerts
|

EEG alpha power and alpha power asymmetry in sleep and wakefulness

Abstract: Asymmetry of waking electroencephalography (EEG) alpha power in frontal regions has been correlated with waking emotional reactivity and the emotional content of dream reports. Little is known regarding alpha asymmetry during sleep. The present study was performed to compare alpha power and alpha power asymmetry in various brain regions across states of sleep and wakefulness. Waking and sleep EEG were recorded in a group of patients undergoing polysomnographic evaluation for possible sleep disorders. Alpha EEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 36 publications
(19 reference statements)
1
34
1
1
Order By: Relevance
“…According to the wakefulness literature, an increase in alpha power would rather be associated with cortical inhibition than with cortical excitation. In agreement with this hypothesis, Benca et al (1999) suggested that increased alpha power might represent cortical deactivation during sleep. If we interpret our results in line with the latter hypothesis, the increased alpha power in response to first names would be associated with an inhibition process resulting in a diminished processing of the first names.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…According to the wakefulness literature, an increase in alpha power would rather be associated with cortical inhibition than with cortical excitation. In agreement with this hypothesis, Benca et al (1999) suggested that increased alpha power might represent cortical deactivation during sleep. If we interpret our results in line with the latter hypothesis, the increased alpha power in response to first names would be associated with an inhibition process resulting in a diminished processing of the first names.…”
Section: Discussionmentioning
confidence: 69%
“…However, few studies investigated alpha activity in HR and LR during sleep (Goodenough et al, 1959; Lewis et al, 1966; Dumermuth et al, 1983; Benca et al, 1999; Cantero et al, 2002), and to our knowledge no study investigated alpha activity induced by stimulations during sleep and wakefulness in HR and LR.…”
Section: Introductionmentioning
confidence: 96%
“…The suppression is more pronounced over the left hemisphere (being the dominant hemisphere in all our subjects). Asymmetry of waking EEG alpha power in frontal regions has been correlated with waking emotional reactivity (19). Davidson showed that such symmetry exists in depressed (20) and anxious patients (21).…”
Section: Discussionmentioning
confidence: 99%
“…The state of quiet wakefulness is important for human psy choemotional functions. There are several proofs that the functional organization of the cerebral cortex depends not only on the specific conditions of the envi ronment or definite cognitive tasks but also on stable characteristics reflecting specific features inherent in a person that determine the state of the main structures of the brain providing quiet wakefulness [14][15][16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%